Recent Prehistory enclosures and funerary practices. Some remarks. - Márquez-Romero, José Enrique; Jiménez-Jáimez, Víctor José (BAR, 2014)
Throughout European Recent Prehistory, there was an evident relationship between monumental enclosures and the deposition of human remains. It is true that, at least in the Neolithic of Western Europe, death was ubiquitous, that is, rituals of death were not anchored to any particular kind of context, but they moved between contexts (Thomas 2000). However, there is a particularly strong and intriguing connection between human bones and Prehistoric enclosures that undoubtedly deserves close attention. Moreover, the questions that arise from this relation have not been systematised yet, let alone explicitly formulated. This is why the celebration of a meeting on the matter, organised by ERA Arqueologia and the Gulbenkian Foundation and held in Lisbon (November 2012), was fully justified. In this concluding chapter, we will highlight and explore what we think are the two main topics discussed in such conference and compiled in the present volume: 'Recent Prehistory Enclosures', on one side, and 'Funerary practices', on the other, thus coinciding with the meeting title. We will finish with a few comments of our own on both issues.
Política de acceso abierto tomada de: https://www.barpublishing.com/pdf/Self-Archiving%20Guidelines%2014.07.2023%20V2.pdf ‘This is an Accepted Manuscript version of a chapter published by BAR Publishing. This version is free to view and download for personal use only. It cannot be reproduced in any form without permission of the publisher.
Keywords: Restos arqueológicos; Monumentos funerarios; Península ibérica; Calcolítico; Recintos de fosos; Neolítico; Arqueología funeraria